TYPES OF DIRECTIVE SPEECH ACTS FOUND IN “THE SEA BEAST” MOVIE - Hasra, Sulvira; Nur, Sahril; Fitriyani, Fitriyani (Faculty of Languages and Literature, Universitas Negeri Makassar, 2024)
Based on this descriptive research, the research formulates two research questions as follows: 1. What directive speech acts are linguistically used by the main character in the